Implementation of Digital Marketing Strategies through Social Media Marketing, Supply Chain Management and Online Sales of Bill Chilly Product - Bambang Dwi Hartono; Budi Permana Yusuf; Angia Arifiati (International Journal of Supply Chain Management, 2020)
This research discusses the implementation of digital marketing strategies through social media marketing and online sales at the startup business of Chilly Bin products. Nowadays, companies have to market their products and services through digital marketing online without also leaving offline sales. The study enumerates that supply chain management has a significant impact on new business products. Companies that use digital marketing as a promotion strategy either with social media or online sales can increase company revenue or enhance consumer purchasing decisions. The overall data obtained from the online users of marketing and sales and PLS-SEM was employed to test the hypotheses. Here the researchers strive to recommend marketing strategies through social media and marketing strategies applied to sell products online. There are still many marketing channels that have not well utilized for consumers to aware, appeal, ask, act and advocate. Marketing 4.0 integrates forms of online and offline sales. The most important thing is that which is easily found on the internet that drives consumers to know and to buy products resulting in more profits. Selling and promoting products must be attractive, up to date, follow the trends, and increasing e-commerce marketplaces and social media usage.